2003
DOI: 10.1038/sj.npp.1300027
|View full text |Cite
|
Sign up to set email alerts
|

H1-Histamine Receptor Affinity Predicts Short-Term Weight Gain for Typical and Atypical Antipsychotic Drugs

Abstract: As a result of superior efficacy and overall tolerability, atypical antipsychotic drugs have become the treatment of choice for schizophrenia and related disorders, despite their side effects. Weight gain is a common and potentially serious complication of some antipsychotic drug therapy, and may be accompanied by hyperlipidemia, hypertension and hyperglycemia and, in some extreme cases, diabetic ketoacidosis. The molecular mechanism(s) responsible for antipsychotic drug-induced weight gain are unknown, but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
494
1
12

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 703 publications
(537 citation statements)
references
References 34 publications
16
494
1
12
Order By: Relevance
“…Allison et al (1999) stressed the importance of using a random effects model, and concluded that the 'most reasonable estimates' were the estimated weight changes after 10 weeks of treatment derived from a random effects model. However, rather surprisingly, none of the weight gain data cited by Kroeze et al (2003 , Table 1) were derived from this specific recommended index. Instead, some data were derived from index (i), for example data for loxapine and molindone; some from index (ii), for example data for risperidone and thioridazine; and some from index (iii), for example data for chlorpromazine and clozapine.…”
Section: Sirmentioning
confidence: 94%
See 3 more Smart Citations
“…Allison et al (1999) stressed the importance of using a random effects model, and concluded that the 'most reasonable estimates' were the estimated weight changes after 10 weeks of treatment derived from a random effects model. However, rather surprisingly, none of the weight gain data cited by Kroeze et al (2003 , Table 1) were derived from this specific recommended index. Instead, some data were derived from index (i), for example data for loxapine and molindone; some from index (ii), for example data for risperidone and thioridazine; and some from index (iii), for example data for chlorpromazine and clozapine.…”
Section: Sirmentioning
confidence: 94%
“…In their report, Kroeze et al (2003) conclude that antipsychotic-induced weight gain is mainly due to H 1 receptor antagonism. They suggest that 'The next generation of antipsychotic drugs be screened to avoid H 1 -histamine receptors'.…”
Section: Sirmentioning
confidence: 97%
See 2 more Smart Citations
“…The inhibition of the H 1 receptors is directly involved in the activation of hypothalamic AMPK signaling, which stimulates food intake and positive energy balance and reverses the anorexigenic effect of leptin [36]. A strong link between the H 1 receptor affinity of antipsychotic agents and their weight gain propensity has been reported [39]. Clozapine and olanzapine which have higher affinity for the H 1 receptors ( K i  = 1.2 nM and K i  = 2.0 nM, respectively) showed a greater propensity to induce weight gain [40,41].…”
Section: Introductionmentioning
confidence: 99%